Terminologia da indústria do alumínio - MARTINS, Arlon Francisco Carvalho (2007)
This work is based on two theoretical tendencies in terminology - The Socioterminology and the Communicative Theory of Terminology. It describes and presents under the form of an electronic and printed glossary the technical language of the ALBRAS Alumínio Brasileiro S.A, the biggest aluminum producer industry of the north of Brazil. All the terms were drawn from 53 specialized texts distributed according to seven operational areas of the company. We extracted not only the technical terms, but also their definitions and their contexts of occurrence. For a quantitative and a qualitative improvement of the repertory we elaborated a list of the collected terms and we interviewed 20 members of the company staff. The main objective of the interviews was to complement the information related to the definitions and to the contexts. We used a software called Lexique-Pro to automatically organize the glossary in alphabetical order. After elaborating the first version of the glossary, we asked specialists to check and confirming the information. The final version of the repertory has 640 entrances that represent a broad universe of the present technical language of the metallurgy of the aluminum. Although we assume the exhaustive propose of this work, it does not represent the totality of the corresponding technical terms of this area of knowledge. We presented the terminological units, describing their function through the attributions of definition and verifying their real uses through contexts. Thus, we presents the Terminological Glossary of the Aluminum Industry as an important tool both for the professionals of this area and for other professionals interested in the language of this human activity.